Removal of lead ion from industrial wastewater by using date palm seeds as a low-cost adsorbent - Maki, Anwar A.; Abdulnabi, Zuhair A.; Mahdi, Bayan A.; Al-Taee, Asaad M.R.; Al-Anber, LUMA J.M. (Mesopotamian Journal of Marine Sciences, 2020)
Date palm (Phoenix dactylifera L.) seeds were used as an adsorbent product to remove lead ions from aqueous solutions through the batch adsorption process. In this study, the optimum condition used to determine the adsorption of industrial wastewater were including pH, temperature, agitation speed and contact time. The results were evaluated by using seeds of two date palm cultivars (Hillawi and Zahdi) The results showed that, the highest removal ratio of lead ions from industrial wastewater samples achieved by Hillawi seeds was 0.598 mg/g, 79.81% at time 90 min., pH 6.5, agitation speed 50 rpm and Temp. 25°C. While Zahdi seeds had given the results of 0.349 mg/g, 43.65% at Time 90 min., pH 4.5, agitation speed 200 rpm and Temp.35°C. Surface morphology and functional surface groups were determined by using Scanning Electron Microscopy and Infrared Spectroscopy (FT-IR), respectively.